Amnesia, Anesthesia, and Warranted Fear - Carbonell, Vanessa (2014)
Is a painful experience less bad for you if you will not remember it? Do you have less reason to fear it? These questions bear on how we think about medical procedures and surgeries that use an anesthesia regimen that leaves patients conscious – and potentially in pain – but results in complete ‘drug-induced amnesia’ after the fact. I argue that drug-induced amnesia does not render a painful medical procedure a less fitting object of fear, and thus the prospect of amnesia does not give patients a reason not to fear it. I expose three mistakes in reasoning that might explain our tendency to view pain or discomfort as less fearful in virtue of expected amnesia: a mistaken view of personal identity; a mistaken view of the target of anticipation; and a mistaken method of incorporating past evidence into calculations about future experiences. Ultimately my argument has implications for whether particular procedures are justified and how medical professionals should speak with anxious patients about the prospect of drug-induced amnesia.
Keywords: Fear; Derek Parfit; sedation; midazolam; Personal Identity; anesthesia; amnesia